The Potential of Fintech in Enhancing the Use of Salam Contract in Islamic Banking - Muneeza, Aishath; Mustapha, Zakariya (International Journal of Islamic Economics and Finance (IJIEF), 2020)
An Islamic banking system employs different Shariah contracts to develop and offer products and services in different jurisdictions. One of such contracts is salam which is a forward sale contract. This study aims to examine the practice of salam as an instrument of Islamic banks financing and how technology can be used to enhance its application thereto. A qualitative approach is employed in this research where primary data sources on salam contract were examined, along with content analysis of relevant secondary data sources on the contract and how its practiced in Islamic banking. In furtherance of that practice, salam instrument can be leveraged on technology, mainly the blockchain. This would enhance its operation by bringing about automation, transparency, fair pricing, saving time and cost as well as enabling widespread access of Islamic bank financing to smaller enterprises to promote societal well-being. This research reveals that salam instruments cater for different clients’ needs and enjoy patronage in many jurisdictions even though it is currently the least utilized contract in Islamic banks financing due to divergence of juristic views on its general permissibility. Also, salam is an exceptional contract for Islamic banks financing of agriculture and related enterprises among others. The research offers an insight for Islamic banks to leverage on technology in utilizing salam contract towards providing financing for variety of clients, particularly poor farmers. Similarly, jurisdictions not practicing salam stand to learn of the benefits of using salam to offer technologically innovative yet affordable Islamic banking products/services for variety of clients.